Direct shear behavior of cementitious mortar reinforced by carbon fiber textile. (20th July 2020) - Dinh, Ngoc Hieu; Tran, Hai Van; Choi, Kyoung-Kyu
Highlights: Direct shear behavior of Textile-reinforced cementitious mortar was investigated. The TRM material showed ductile behavior when subjected to direct shear. A crack-shear slip model for TRM was developed and verified with the test results. Abstract: This study experimentally investigated the characteristics of carbon fiber textile-reinforced mortar (TRM) under direct shear. The main test parameters of this study include the fiber reinforcement ratio of carbon fiber textile, the surface treatment used between mortar matrix and the fiber textile, and the inclination angle of the fiber filaments. Three fiber reinforcement ratio of carbon fiber textile of (0.17, 0.35, and 0.53) % in the mortar matrix were investigated. Two different surface treatment methods were employed to improve the bond performance of carbon fiber textiles in the mortar matrix: epoxy impregnation only, and sand coating after epoxy impregnation. Two inclination angles of fiber filaments of 0°/90° and –45°/45° were investigated. The test results showed that the textile reinforcement within cementitious mortar matrix affected the failure modes and the shear performance of test specimens in terms of cracking and ultimate shear stress, crack deformation, and residual shear stress in the pre- and post-peak stages. Moreover, a crack-shear slip model for cementitious mortar reinforced by carbon fiber textile was developed considering the material characteristics of the mortar and the fiber textile, and its prediction showed good agreement with the experimental results.